Critical factors leading to wound complications in amputated patients: low hematocrit levels - Omeroglu, Sinan; Demir, Ibrahim; Beyaz, Metin O. (International Surgery Journal, 2020)
Background: Patients with diabetes-induced lower extremity infection and gangrene suffer from post-amputation wound complications. The aim of this report is to identify critical factors leading to wound complications in amputated patients. Methods: 50 patients with ipsilateral transmetatarsal (TMA) or finger amputation treated in Istanbul University Medical Faculty between 2001 and 2013 were retrospectively reviewed. Amputations were caused by diabetic foot infection. None of the patients had peripheral artery disease (ABPI>1.1). Results: In 9 (18%) patients, revision was required despite appropriate antibiotherapy after amputation. 7 (78%) of these patients were women, 8 (89%) were smokers and hematocrit levels were below 25% in all of them. 4 of the 5 patients (80%) with chronic kidney disease were among the patients in need of revision. Conclusion: The risk of wound complications after amputation is high. These complications increase morbidity and treatment costs. This study showed that low hematocrit value is a risk factor for the development of wound infection after amputation.